KOMPENSASI DAN PENGEMBANGAN KARIR BERPENGARUH TERHADAP KEPUASAN KERJA DAN RETENSI KARYAWAN BPR LESTARI - Wirayudha, Cokorda Alit; Adnyani, I Gusti Ayu Dewi (E-Jurnal Manajemen; Vol 9 No 5 (2020), 2020)
Employee retention in a company or institution is illustrated by compensation, career development and job satisfaction. Compensation and career development provided will increase job satisfaction so that there is  sense of staying longer in the company. The purpose of this study was to determine the effect of compensation and career development on job satisfaction and employee retention. This research conducted at BPR Lestari Teuku Umar Denpasar. The sample were 83 people through Simple Random Sampling. Data collection through interviews and questionnaires. Path analysis is used. Career compensation and development have positive effect on job satisfaction. Compensation, career development and job satisfaction have positive impact on employee retention. Jo  satisfaction mediates effect of compensation on employee retention, and job satisfaction mediates effect of career development on employee retention. When compensation and career development obtained by employees increase job satisfaction so that it has the potential to increase employee retention. Keywords: compensation, career development, job satisfaction, employee retention